Analisa Dampak Intensitas Kebisingan Terhadap Operator Mesin Penggiling Kacang Tanah - Corry Handayani; Lilia Trisyathia Quentara; Hardianto (Jurnal INOVATOR, 2020)
Indonesia there are many abundant produce mainly the agriculture not dependent with one example is peanuts.The fields are in need of peanuts as a raw material for the manufacture of cheese, butter, oil, jam, candy or other food.To facilitate the work of the man in the beans then grind in a grinder machine make peanuts.At this point has created peanut grinder machine automatic movements using electric motor.This research was conducted to find out perbedan the intensity of noise and impact on the impact of the use of the old engines with new engines.The data obtained from the measurement of the intensity of the noise using the android application and filling the questionnaires by respondents.Based on statistical tests Paired Sample t-Tests on the get that there was a decrease in the intensity of the noise of 33.60%.Test validity and reliability the questionnaire stated 7 questions (old machine) and 13 questions (new machine) in kuesiner is valid because r count > r tables, and the results of Chronbach's > 0.60 Alpha so in say reliability.From the comparison of the data of the questionnaire can be seen with the new engines occurred quite a significant difference in the comfort of the operator's wor